UTILIZATION OF SUCKERMOUTH CATFISH (Pterygoplichthys pardalis) AS A RAW MATERIAL OF PROTEIN IN ARTIFICIAL FEED TILAPIA: PEMANFAATAN IKAN SAPU-SAPU (Pterygoplichthys pardalis) SEBAGAI BAHAN BAKU SUMBER PROTEIN DALAM PAKAN BUATAN IKAN NILA - Surianti, Surianti; Damis, Damis; Wahyudi, Wahyudi; Febrian, Muh Rizal; Sulaiman, Muhammad Anugrah (Jurnal Teknologi Perikanan dan Kelautan, 2025)
In aquaculture, feed constitutes approximately 60% of the total production cost. The feed efficiency can be enhanced by utilizing local ingredients, such as suckermouth catfish (Pterygoplichthys pardalis) meal, as an alternative to imported fish meal. This study aims to evaluate the effects of varying substitution levels between local fish meal and suckermouth catfish meal on the growth performance and digestive enzyme activity of Nile tilapia (Oreochromis niloticus). A Completely Randomized Design (CRD) was applied with five treatments and three replications: A (100% local fish meal:0% suckermouth catfish meal), B (75%:25%), C (50%:50%), D (25%:75%), and E (0%:100%), resulting in a total of 15 experimental units. Test fishes with an initial weight of 1.5 g/individual of fish were stocked as many as 20 individual of fish in a plastic bucket containing 85 L of air per unit. Fish were fed 6% of their body weight per day with two feedings in the morning and evening for 60 days. Variables were analyzed using analysis of variance (ANOVA), statistical tests were performed at a significance level of 5% (α = 0.05) with a 95% confidence interval. The results showed that treatment D (25% local fish meal: 75% suckermouth catfish meal) had the best significant effect (p = 0.004) on weight gain of 3.9±0.83 g, treatments A, B, C and E were the same but different from treatment D, while for digestive enzyme activity, namely protease of 0.452 U/mL and amylase of 0.579 U/mL.